Comparative Study of the Seismic Performance of Tubular Frame, Diagrid, Pentagrid, and Hexagrid Structural Systems using ETABS - Robin Singh, Barkha Verma (Mathematical Statistician and Engineering Applications, 2023)
The construction of multi-story buildings is rising quickly over the world. Taller buildings utilise the land more effectively than low-rise buildings, however as a building’s height increases, lateral load-resisting systems become more necessary than gravity loads. To enhance the structural performance of tall structures in both lateral and gravity loads, various structural systems have recently been introduced. The current study aims to perform a seismic analysis using the response spectrum method on a multistory steel tube building with various structural systems, which include tubular frame, diagrid, pentagrid, and hexagrid. To achieve this, ETABS V.19 is used to design and analyse steel tube buildings. Models for seismic zone-V are compared for result parameters which include storey displacement, storey drift, and storey shear.